Synthesis of H-Pyrazolo[5,1-a]isoquinolines via Silver(I)-Catalyzed Tandem Reaction of N′-(2-Alkynylbenzylidene)hydrazides with Propargyl Amine Derivatives - Liu, Hongliang; Wang, Zhiyong; Pu, Shouzhi; Liu, Gang (Synthesis, 2014)
We have developed a tandem reaction of N′-(2-alkynylbenzylidene)hydrazides with propargyl amine derivatives catalyzed by silver triflate to provide 2-(aminomethyl)-H-pyrazolo[5,1-a]isoquinolines. This reaction proceeds through a tandem 6-endo-cyclization, nucleophilic addition, 5-endo-cyclization and aromatization, leading to the cycloadducts in moderate to good yields with exclusive regioselectivity.
Keywords: N′-(2-alkynylbenzylidene)hydrazides; propargyl amine derivatives; silver triflate; tandem reactions; 1,3-dipolar cycloaddition reactions